Reconstruction from local government into village government financial accounting in Indonesia - Matjuri, Matjuri; Suyudi, Muhamad (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2018)
The research objectives are: (a) adopting local government financial accounting into village government financial accounting, (b) reconstructing the understanding of human resources on implementation of local government financial accounting into the implementation of village government financial accounting, and (c) understanding the capacity of village resources to implement village government accounting. This research uses a qualitative approach. The analytical tool adapted from Freud through (a) observation, effort to build perceptions based on observed observations in the field, (b) interviews, in-depth interviews with informants (to villages and village secretaries), and (c) documentation, declaring and documenting the past events. The findings show that the positive attitude shown by Rappoa's government apparatus is followed by positive behavior. It indicates that attitudes and behaviors demonstrated by village government and its apparatus are responsive. All government regulations, both from central government, provincial and local governments and even sub-district government must be followed by below government. The positive attitude of the village as the lowest government level should implement all the laws and regulations.